Photopheresis Provides Significant Long-Lasting Benefit in Nephrogenic Systemic Fibrosis - Ranran Zhang; William Nicholas Rose (Case Reports in Dermatological Medicine)
Nephrogenic systemic fibrosis (NSF), previously known as nephrogenic fibrosing dermopathy, is a rare complication of exposure to gadolinium-based contrast agents in patients who have significantly decreased renal function. Manifestations include fibrosis of the skin and other tissues. Effective therapies are lacking. Photopheresis has been tried with variable rates of improvement, and small numbers of cases (20 as of 2016) have been reported of NSF patients treated with photopheresis. We report a case of patient with nephrogenic systemic fibrosis who was treated with photopheresis and demonstrated significant lasting improvements.